PENGEMBANGAN PERANGKAT PEMBELAJARAN PROJECT-BASED LEARNING UNTUK MEMBEKALI FOUNDATIONAL KNOWLEDGE DAN MENINGKATKAN SCIENTIFIC LITERACY - Ricka Tesi Muskania; Insih Wilujeng (Jurnal Cakrawala Pendidikan, 2017)
Penelitian ini bertujuan untuk mengetahui: (1) kelayakan perangkat pembelajaran IPA berbasis project-based learning, (2) pengaruh penerapan perangkat pembelajaran IPA berbasis project-based learning terhadap keterbekalan digital/ICT literacy, (3) pengaruh penerapan perangkat pembelajaran IPA berbasis project-based learning terhadap scientific literacy peserta didik SMP. Penelitianinimerupakanpenelitiandanpengembangandenganmenggunakan model Borg Galldengan prosedur yangmeliputi (1) studipendahuluan, (2) desainproduk, (3) validasi, (4) ujicobadanrevisiprodukhinggamenghasilkanprodukakhir. Hasilpenelitianiniadalahkelayakanperangkatpembelajaran IPA berbasisproject-based learningyang dihasilkan memperoleh kriteriabaik sekali.Keterbekalanfoundational knowledge khusus digital/ICT literacysebesar 98,29%. Kriteriabaiksekalidiperolehuntukpeningkatanscientific literacy pesertadidik SMP setelahmengikutipembelajaranmenggunakanperangkatpembelajaran IPA berbasisproject-based learningdengangain scoresebesar 15,37. Hasilujiindependent-sample t testmenunjukkanbahwaperangkatpembelajaranberbasisproject-based learningmemberikanpengaruhsignifikanterhadapscientific literacypesertadidik SMP. Kata kunci: perangkat pembelajaran IPA, project-based learning, digital/ICT literacy, scientific literacy AbstractThis study aims to: (1) the result feasibility of the project-based science teaching kit, (2) the implementation effect of project-based science teaching kit on the digital/ICT literacy provision, and (3) the implementation effect of project-based science teaching kit on the improvement of scientific literacy of junior high school students.This was a research and development (RD) study employing the development model of Borg Gall with a procedure consisted of: (1) preliminary study, (2) product design, (3) validation, (4) tryout and revision to final product study.The result of the study is a project-based science teaching kit the feasibility product criteria being “very good”. The provision of foundational knowledge special digital/ICT literacy as is much as 98.29%. The improvement of scientific literacy is in the “very good” category after they attend teaching activities implementing the project-based science teaching kit with the gain score of 15.37. The result of independent-sample t test shows that the developed project-based science teaching kit gives a significant effect to the increase of the scientific literacy of junior high school students. Keywords: science teaching kit, project-based learning, digital/ICT literacy, scientific literacy